Efficiency Analysis of Compression Software (WINRAR and 7-Zip) Across Diverse Data Types on Windows 11 and Ubuntu 23.10 - Rakha Maulana; Bahteramon Bintang Sanjaya Manurung; Nathanael Berliano Novanka Putra; Aqwam Rosadi Kardian (Jurnal Info Sains : Informatika dan Sains, 2023)
This paper presents a comprehensive analysis of the performance and efficiency of two widely used compression software, WINRAR and 7-Zip, across various data types. The study focuses on evaluating their effectiveness on different operating systems, specifically Windows 11 and Ubuntu 23.10. The analysis encompasses considerations such as compression ratios, resource utilization, and processing times. WINRAR and 7-Zip are examined in diverse scenarios, including the compression of text files (.txt), image files (.png), audio files (.flac), and video files (.mp4). The study reveals notable variations in compression outcomes influenced by intrinsic complexities of each file format. Moreover, the investigation extends beyond the initially studied operating systems, suggesting potential applications on other platforms like Kali Linux. The findings contribute insights into the nuanced performance of compression software across varied data types and operating environments, facilitating informed decision-making for users seeking optimal compression solutions.